The Combination of Low-Frequency Ultrasound and Antibiotics Improves the Killing of In Vitro Staphylococcus aureus and Pseudomonas aeruginosa Biofilms - Lasse Kvich; Mads H. Christensen; Malgorzata K. Pierchala; Konstantin Astafiev; Rasmus Lou-Moeller; Thomas Bjarnsholt (MDPI AG, 2022)
Due to an increase in underlying predisposing factors, chronic wounds have become an increasing burden on healthcare systems worldwide. Chronic infections often contain biofilm-forming bacteria, which are challenging to eradicate due to increased antibiotic tolerance; thus, new and improved therapeutic strategies are warranted. One such strategy is the combination of ultrasound and antibiotics. Therefore, this study aimed to investigate the combinatory effects of low-frequency (50 kHz) ultrasound delivered by specially designed ultrasound patches using flexible piezoelectric material, PiezoPaint™, in combination with antibiotics against biofilms with Staphylococcus aureus and Pseudomonas aeruginosa. The reduction in viable cells in S. aureus and P. aeruginosa biofilms was evaluated post-treatment with fusidic acid, clindamycin, ciprofloxacin, and colistin in combination with ultrasound treatment. Two-hour ultrasound treatment significantly increased the bactericidal effect of all four antibiotics, resulting in a 96-98% and 90-93% reduction in P. aeruginosa and S. aureus, respectively. In addition, an additive effect was observed when extending treatment to 4 h, resulting in >99% and 95-97% reduction in P. aeruginosa and S. aureus, respectively. These results contrasted the lack of effect observed when treating filter-biofilms with antibiotics alone. The combined effect of ultrasound and antibiotic treatment resulted in a synergistic effect, reducing the viability of the clinically relevant pathogens S. aureus and P. aeruginosa. The modularity of the specially designed patches intended for topical treatment holds promising applications as a supplement in chronic wound therapy. Further studies are warranted with clinically isolated strains and other clinically relevant antibiotics before proceeding to studies where safety and applicability are investigated.